The Influence of Convergent Thinking Style toward The New Environmental Paradigm (NEP) (Experimental Study to students of Biology Program of Sultan Ageng Tirtayasa University in 2019) - Enggar Utari (Universitas Sultan Ageng Tirtayasa, 2019)
The study focused on the Students’ New Environmental Paradigm (NEP) influenced by convergent thinking style. The method of the study was experimental. The study was conducted from May at Sultan Ageng Tirtayasa University, Banten. The data were collected through purposive sampling consisted of 44 students given. The research finding the students’ NEP based on high convergent thinking style were better than those who got low convergent thinking style Keywords: Convergent Thinking Style, The New Environmental Paradigm (NEP) of Students